Implementation of Simple Additive Weighting Method as a Decision Support for New Student Admission in Madrasah Aliyah - Frisma Handayanna; Fatmala Dewi (Jurnal Riset Informatika, 2020)
The selection or acceptance of new students is something that needs to be determined quickly. In terms of the determination of prospective new students, several considerations are needed which are quite numerous and complicated, namely, the standard of grades, school entry requirements, and policies of the government and educational institutions that often change each year. In terms of the admission of new students, students are required to come directly. During this time the process of admission test for new students is still using the manual method by filling out the answer sheet provided by the committee. The method used in determining students to be accepted is Simple Additive Weight. Determining the admission of new students using the Simple Additive Weight method, where this method provides certain criteria which have a weight value of each so that the results of the sum of the weights will get the final decision and rank the students accepted at Madrasah Aliyah named Amira and Afrilina.